International business growth: The leveraging effect of collaborative research networks capabilities - Abrantes, B. F.; Quintas, J.; Wegner, D.; António, N. (International Journal of Business Competition and Growth, 2024)
In this research, we examine the capabilities built by multinational enterprises (MNEs) in a consortium and the performance implications of such capability-building on international business growth. We followed a research avenue with a sparse scholarly track, as one delved into a subset of network-types (CRNs) on a certain organisational-typology (i.e., consortiums); and furthermore exploring it within the energy sector in EU. The methodological procedure (content analysis) allowed us the building of a road-map of international business competences (IBC) gained by these multinational enterprises (MNEs) and their effects on their international business growth (IBG). Open and axial coding, and an inferential exercise upon data outputs, uncovered a new form of collaborative networks (CN) amalgamating features of atomised and piloted CNs.